Dari Perahu Sri Komala Hingga Puputan; Perlawanan terhadap Pemerintahan Hindia Belanda 1906 - Mirawati, Inna (Citra Lekha, 2013)
This research discusses the kingdom of Badung in Bali resistance against the Dutch that lasted six days, starting from December 15 until September 20, 1906. That event was known as Puputan. The main cause of this opposition stemmed from Sri Komala stranded boat on the beach of Sanur. The Dutch considered the king of Badung should responsibile towards this event. So this research entitle "From Boat Sri Komala until Puputan: Kingdom of Badung, Bali Resistance against Dutch colonialism in 1906. This research has calculated using historical methods, including heuristics, criticism, synthesis and historiography. Researcher also used a theory of Collective Behavior by Neil J. Smelser to analyzed research problems. It founds that the resistance was motivated by political ambition and intervention of the Dutch to colonized the whole of Bali areas. The Badung kingdom argued that it was better to combat than bear their shame. This decision has logical consequences of the King in emergence of a critical attitude by addressing the situation of the kingdom at that time. Meanwhile, the Dutch blockade access of the Badung kingdom that would not lose money to pay compensation Sri Komala boat owners.The uniqueness of this resistance there were critical attitudes and methods clashed as a final option in their war. In Puputan both the king of Badung and the Dutch were equally experienced defeat. Keyword: Puputan, Sri Komala boat, resistence